Pengaruh Gerak Dan Lagu Kristiani Terhadap Ekspresi Bahagia Anak Usia 5-6 Tahun Di TK GKPI Tarutung Kota (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
The aim of this research is to determine the influence of Christian movements and songs on the happy expressions of children aged 5-6 years at the GKPI Tarutung City Kindergarten. The type of research used in this research is quantitative research with experimental research methods and the type of research design is one group pretest post-test design. The population in this study was all children aged 5-6 years at GKPI Tarutung City Kindergarten, totaling 110 people, and the sampling technique, namely purposive sampling, was 18 children from class B4. Data collection techniques were carried out using observation sheets and documentation. Based on the recapitulation of data on children's happy expressions before being given treatment (pretest) using movements and Christian songs, there were 16.7% in the quite happy (CB) category, 22.2% in the Happy (B) category, and 61.1% in the very happy (SB) category. And after being given treatment (post-test) using movement and Christian songs, there were 5.6% in the quite happy (CB) category, none in the Happy (B) category and 94.4% in the very happy (SB) category. Furthermore, based on the results of the t test, the value of tcount≥ttable was obtained (3.610 > 1.740). So it can be concluded that H0 is rejected and Ha is accepted, which means that there is an influence of movements and Christian songs on the happy expressions of children aged 5-6 years at the GKPI Tarutung City Kindergarten.